DOES FREE WILL EXIST?. Issue 42 (9th December 2015) - Johnson, David Kyle
Abstract : In 'Do Souls Exist', I suggested that, while the non-existence of the soul does threaten free will, the threat it possess is inconsequential. Free will faces so many other hurdles that, if those were overcome, the soul's non-existence would be a non-threat. In this paper, I establish this; and to do so, I define the common libertarian notion of free will, and show how neuroscience, determinism, indeterminism, theological belief, axioms in logic, and even Einstein's theory of relativity each entail that libertarian free will does not exist. I conclude by demonstrating why some philosophers reject alternate (compatibilist) understandings of free will, and so believe that the notion we are free is an illusion.